2018
DOI: 10.3748/wjg.v24.i30.3448
|View full text |Cite
|
Sign up to set email alerts
|

Altered oral microbiota in chronic hepatitis B patients with different tongue coatings

Abstract: AIMTo elucidate tongue coating microbiota and metabolic differences in chronic hepatitis B (CHB) patients with yellow or white tongue coatings.METHODSTongue coating samples were collected from 53 CHB patients (28 CHB yellow tongue coating patients and 25 CHB white tongue coating patients) and 22 healthy controls. Microbial DNA was extracted from the tongue samples, and the bacterial 16S ribosomal RNA gene V3 region was amplified from all samples and sequenced with the Ion Torrent PGM™ sequencing platform accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
6
24
0
1
Order By: Relevance
“…As reported, yellow tongue was associated with higher HBV titers compared with those in patients with a white tongue. Moreover, a significant decrease in Bacteroidetes and an increase in Proteobacteria was found in HBV-associated yellow tongues, which also showed a selective enrichment of the metagenomic pathways involved in amino acid metabolism, consistent with the metabolic disorder of these patients (129).…”
Section: Modulation Of the Commensal Microbiota By Virusessupporting
confidence: 54%
“…As reported, yellow tongue was associated with higher HBV titers compared with those in patients with a white tongue. Moreover, a significant decrease in Bacteroidetes and an increase in Proteobacteria was found in HBV-associated yellow tongues, which also showed a selective enrichment of the metagenomic pathways involved in amino acid metabolism, consistent with the metabolic disorder of these patients (129).…”
Section: Modulation Of the Commensal Microbiota By Virusessupporting
confidence: 54%
“…Tongue coating is one of the important foundations of TCM syndrome signature. Zhao et al [19, 20] demonstrated microbiota and metabolic difference of CHB patients with different TCM syndromes. Above all, biomolecules (including genes, proteins, and metabolites) expression and regulation rules were researched with the laws and methods in genomics, proteomics and metabonomics.…”
Section: Introductionmentioning
confidence: 99%
“…Combining metabolome and microbiome data has resulted in some exciting findings in health and disease (Zhao et al, 2018). Herein, we observed the significant correlation between subgingival microbiota genera and metabolites of GCF using correlation analysis.…”
Section: Discussionmentioning
confidence: 81%